Chemotherapy and glycemic control in patients with type 2 diabetes and cancer: A comparative case analysis - Denise Soltow Hershey; Sarah Hession (Elsevier, 2017)
Objective: Individuals with diabetes who develop cancer have a worse 5-year overall survival rate and are more likely to develop an infection and/or be hospitalized when compared to those without diabetes. Patients with diabetes and cancer receiving chemotherapy have an increased risk for developing glycemic issues. The relationship between chemotherapy and glycemic control is not completely understood. The aim of this study was to explore the relationship between glycemic control, symptoms, physical and mental function, development of adverse events, and chemotherapy reductions or stoppages in adults with Type 2 diabetes (T2D) and cancer. Methods: A prospective 12-week longitudinal cohort study recruited 24 adults with T2D, solid tumor cancer, or lymphoma receiving outpatient intravenous chemotherapy. Eighteen individuals completed baseline data and were included in the analysis. A comparative case analysis was performed to analyze the results. Results: Potential predictors of occurrence of an adverse event include sex (relative risk [RR] = 1.5), treatment with insulin (RR = 2.17), years with diabetes (RR = 3.85), and baseline glycated hemoglobin (HbA1c) (odds ratio [OR] = 1.67). Baseline body mass index (BMI) (OR = 1.16) and HbA1c (OR = 1.61) were potentially predictive of a chemotherapy stoppage. Conclusions: Level of glycemic control at the time an individual begins treatment for cancer appears to contribute to the occurrence of an adverse event, developing an infection and/or being hospitalized during treatment, and the increased risk of having a chemotherapy reduction or stoppage. Clinicians working with patients receiving chemotherapy for a solid tumor cancer who have pre-existing diabetes, need to be aware of how the patients glycemic level at the start of treatment may impact successful treatment completion.